2021
DOI: 10.1289/ehp8368
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Fine Particle Elemental Components and Natural and Cause-Specific Mortality—a Pooled Analysis of Eight European Cohorts within the ELAPSE Project

Abstract: Background: Inconsistent associations between long-term exposure to particles with an aerodynamic diameter [fine particulate matter ( )] components and mortality have been reported, partly related to challenges in exposure assessment. Objectives: We investigated the associations between long-term exposure to elemental components and mortality in a large pooled European cohort; to compare health effects of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 59 publications
7
52
0
Order By: Relevance
“…The ESCAPE study also reported an association between PM 2.5 sulfur and all-cause mortality independent of PM 2.5 mass exposure [52]. In a pooled analysis of eight of the European ESCAPE cohorts, residential exposure to the 2010 annual average concentration of eight PM 2.5 components (Cu, Fe, K, Ni, S, Si, V and Zn) was estimated with Europe-wide models at a 100 × 100 m scale, and all were found associated with all-cause mortality [20]. In two pollutant models, adjusting for PM 2.5 or NO 2 , Ni, S, Si, V and Zn remained associated with all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESCAPE study also reported an association between PM 2.5 sulfur and all-cause mortality independent of PM 2.5 mass exposure [52]. In a pooled analysis of eight of the European ESCAPE cohorts, residential exposure to the 2010 annual average concentration of eight PM 2.5 components (Cu, Fe, K, Ni, S, Si, V and Zn) was estimated with Europe-wide models at a 100 × 100 m scale, and all were found associated with all-cause mortality [20]. In two pollutant models, adjusting for PM 2.5 or NO 2 , Ni, S, Si, V and Zn remained associated with all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis also found support for associations between Fe, nitrate, Zn, Si and CVD mortality, whereas there were not sufficient number of studies to conduct a meta-analysis for respiratory mortality. Cu, iron (Fe), potasium (K), nickel (Ni), sulfur (S), Si, vanadium (V) and Zn were associated with natural-cause mortality in a pooled analysis of eight European cohorts [20]. Within a recent study of the Danish Diet, Cancer and Health cohort all-cause mortality increased with NO 2 , O 3 , PM 2.5 , BC and secondary organic aerosols (SOA) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest strong effects from primary combustion-related particles, e.g., vehicle exhaust particles, per increase in mass concentration. However, the limited number of studies on PM 2.5 elemental components have produced rather inconclusive results regarding which components are most important for mortality, perhaps because elements such as Fe, Zn, and K may represent different sources in different places [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study, similar to the Medicare population study, found that PM 2.5 mass that contained more sulfates demonstrated greater risk estimates, indicating the importance of PM 2.5 resulting from fossil fuel combustion. The ELAPSE Study subsequently examined this issue in Europe [105]. Pooled data from eight cohorts with 323,782 participants, average age 49 y at baseline .…”
Section: Adverse Health Effects Of Long-term Exposure To Pm Constituent Metals or Source-related Pm Massmentioning
confidence: 99%
“…Other potential toxic constituents including nitrate, sulfate, Zn, Si, Fe, Ni, V, and K were each associated with adverse cardiovascular health, while nitrate, sulfate and V were relevant for adverse respiratory health outcomes. However, the authors' choice to focus on model results simultaneously including particle mass with constituents would be expected to statistically weaken health associations for those that also comprise a significant percent of the mass (e.g., sulfates), as occurred in the Chen et al study [105]. In general, models including both constituents and mass simultaneously, such as conducted here, should be avoided, due to the intercorrelation bias introduced for some, but not all, constituents.…”
Section: Adverse Health Effects Of Long-term Exposure To Pm Constituent Metals or Source-related Pm Massmentioning
confidence: 99%